Two new Asian species of Russula sect. Ingratae with unique basidiospore features for subg. Heterophyllidiae - Ghosh, Aniket; Buyck, Bart; Das, Kanad; Bera, Ishika; Chakraborty, Dyutiparna (European Journal of Taxonomy, 2022)
Two novel species of Russula (Russulaceae, Russulales), namely Russula indosenecis A.Ghosh, D.Chakr., K.Das & Buyck sp. nov. and R. pseudosenecis A.Ghosh, D.Chakr., K.Das & Buyck sp. nov. belonging to sect. Ingratae subg. Heterophyllidiae are proposed herein based on their morphological features and nrITS-based phylogenetic inferences. Both species belong to the Asian ʻR. punctipes-senecisʼ complex of sect. Ingratae. The acrid R. indosenecis was collected from subalpine forests associated with Abies densa, whereas the mild R. pseudosenecis associates with tropical forests dominated by Shorea robusta. Both species are distinct from the other species of this species complex in nrITS sequence data and from all other known species in subg. Heterophyllidiae in the strong amyloidity of their suprahilar spot.